Perioperative and oncological outcomes of single position retroperitoneoscopic radical nephroureterectomy for upper urinary tract urothelial carcinoma - Jiaqiang Chen; Luxin Zhang; Zhihong Dai; Cheng Chang; Heyao Tong; Hepeng Cui; Zhuwei Song; Bo Fan; Zhiyu Liu; Liang Wang (Scientific Reports)
Abstract Radical nephroureterectomy (RNU) is the gold standard therapy for patients with upper urinary tract urothelial carcinoma (UTUC). In this study, we compared the effect of two surgical techniques, single-position complete retroperitoneoscopic radical nephroureterectomy (SCRNU) and laparoscopic nephroureterectomy with open bladder cuff excision (LNOBE), on perioperative and long-term oncological outcomes in UTUC patients. We retrospectively collected information on baseline characteristics, clinicopathological characteristics, surgical approaches, perioperative data, and survival outcomes from 174 patients who underwent RNU for UTUC between January 2018 and June 2023 in our center. The data were analyzed using the Mann-Whitney test, Fisher’s exact test, Chi-square test. Linear regressions were applied to explore the effect of surgery approach on the continuous outcomes. Log-rank test and Kaplan-Meier survival curves were plotted to describe the survival outcome. Univariate and Multivariate Cox regressions were conducted to explore the independent prognostic factors. To address potential selection bias, we also employed an Inverse Probability of Treatment Weighting (IPTW) strategy. Patients who underwent SCRNU had shorter operative times (p < 0.001), reduced estimated blood loss (p < 0.001), less drainage on the first postoperative day (p = 0.009), shorter hospital stays (p = 0.001), and better intravesical recurrence-free survival than those who underwent LNOBE (IVRFS, HR: 0.17, 95% CI: 0.07–0.44, p = 0.007). Moreover, SCRNU was confirmed to be a protective factor for IVRFS after IPTW-adjusted Cox regression analysis was performed (HR: 0.17, 95% CI: 0.04–0.77, p = 0.021). SCRNU not only avoids intraoperative repositioning but also improves perioperative outcomes, including the reduction of operative time, blood loss, and length of hospital stay, and is associated with better IVRFS.